Beobachtungen zum südindischen ländlichen Wochenmarkt - Bohle, Hans-Georg (ERDKUNDE, 1981)
The weekly markets of the study area, the northwestern part of Salem District, have been important trading centres for the last millenium. Today, with one weekly market for every eight villages, rural weekly markets still show a remarkable density in distribution. In recent years, they even seem to have increased in economic importance. By analysing the position of weekly markets within the regional exchange system, three basic functional types are recognized and discussed in case studies. At the lowest order, local weekly markets, not integrated in the regional system of weekly markets, are functioning as small import centres for local consumption goods. In regional weekly markets, however, internal trade becomes the leading function, thus linking the weekly markets of the region into a system. Central weekly markets, on the top of the periodic market hierarchy, play an additional role as important bulking and whole sale centres of agricultural produce for urban supply. For the distinction of the various types of weekly markets, the dominant categories of marketing, trading and servicing participants in these markets are analysed, acting part-time as well as half time of full-time. Regarding the weekly circuits of the professional mobile traders in the study area, a highly complex and integrated pattern of market-rings is recognized. As informal sector institutions par excellence, the rural weekly markets of India may be considered as potential foci for the promotion of rural development programmes that aim at decentralisation as well as participation of the rural poor.